Trabalho infantojuvenil e lutas por direitos nas mesorregiões da Mata e do Agreste da Paraíba (1987-1990) - Estevam, Diognnys Cardoso (2019)
Starting from the research of the Junta de Conciliação e Julgamento de Guarabira (Guarabira Conciliation and Trial Board), linked to the Tribunal Regional do Trabalho da 13ª Região TRT-13 (Regional Labour Court of the 13th Region), corresponding to the State of Paraíba, that are available at the Núcleo de Documentação Histórica do Centro de Humanidades da Universidade Estadual da Paraíba (Historical Documentation Center of the Humanities Center of Paraíba State University) (NDHCH/UEPB), I intend to examine the lawsuits brought by minors and their representatives against their employers in the years 1987 to 1990 seeking enforcement of labor right. The theme about childhood labor in the Mesoregions of Paraiban Mata and Agreste is still little discussed in historiography and the access to this documentation allows us historians broaden the debate about the historical processes lived by minor workers in these regions in the last years of the 1980’s. This work intend to focus on the struggle for guarantee and expansion of child rights post-Military Dictatorship and beginning of Brazilian re-democratization period, paying attetion to the power and social relationships that allowed the exploitation of the children and youth labor force in the region. Thus, the debate keeps around the action that the working class in Paraíba established in the struggle for their rights, and within these actions also will be included the participation of children and young people, the participation of entities such as the Diocese de Guarabira (Diocese of Guarabira) and Movimento de Adolescentes e Crianças (Movement of Adolescents and Children) (MAC), who have observed the issue of poor boys and girls and, finally, the Junta de Conciliação e Julgamento de Guarabira (Guarabira Board of Conciliation and Judgement) as fundamental body for conflict mediation